Analysis of haplotype associated with mutation in a-thalassemia - Sunarto, Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
B-thalassemia is mainly caused by point mutation of B-gene. There are more than 130 mutations, while only a little more than 20 haplotypes in B-gene. Many types of mutation are assosiated with one haplotype. On the other hand, one type of mutation may be associated with more than one chromosome haplotypes. The association of mutation and haplotype raises many questions. An analysis of haplotype has proved to be very useful to discover many aspects of thalassemia. The occurrence of certain mutation in a population might be predicted from the common haplotype of the population. Haplotype has been used to answer the question whether a certain mutation has multiple or single origin; for example the multiple origin of BE-gene in Cambodian population and the single origin of codon 39(CAG -+TAG) are associated with nine different haplotypes in Sardinia. It is suggested that haplotype probably influences the manifestation of thalassemia resulting in thalassemia intermedia.Key words : thalassemia - haplotype - point mutation - recombination - phenotype